Contemporary medical television and crisis in the NHS. Issue 2 (July 2016) - Hamad, Hannah
This article maps the terrain of contemporary UK medical television (TV), paying particular attention to Call the Midwife as its centrepiece, and situating it in contextual relation to the current crisis in the National Health Service. It provides a historical overview of UK and US medical TV, illustrating how medical TV today has been shaped by noteworthy antecedents. It argues that crisis rhetoric surrounding healthcare leading up to the passing of the Health and Social Care Act 2012 has been accompanied by a renaissance in medical TV; and that issues, strands and clusters have emerged in forms, registers and modes with noticeable regularity, especially around the value of affective labour, the cultural politics of nostalgia and the neo-liberalization of healthcare.